2019
DOI: 10.22159/ijcpr.2019v11i6.36339
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices Regarding Vitamin D Deficiency Among Women Attending Imam Hussein Medical City in Karbala 2018

Abstract: Objective: Vitamin D deficiency is a global health problem. It is significantly associated with skeletal and non-skeletal problems. Prevention can be maintained mainly by effective sun exposure or supplementation and to lesser extent by dietary intake. To determine the magnitude of knowledge and practice of women towards vitamin D deficiency. Methods: A cross-sectional study, purposive sample of 442 women were approached who attended consultants’ clinics of Imam Hussein Medical City in Karbala. Data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…So, us study in Iraq found less than half (46.4%) of the subjects were knew that there is a relation between VD and calcium. Little percent (19%) of the subjects had a good level of knowledge (7) .…”
Section: Deficiencymentioning
confidence: 97%
See 4 more Smart Citations
“…So, us study in Iraq found less than half (46.4%) of the subjects were knew that there is a relation between VD and calcium. Little percent (19%) of the subjects had a good level of knowledge (7) .…”
Section: Deficiencymentioning
confidence: 97%
“…Indeed, we would like to point out that, even in the presence of strong and significant associations, a causal role of hypovitaminosis D in facilitating COVID-19 spread» (19) . 5-Association between Level of Knowledge, behavior of study sample there was no significant relationship among studied variable, and level of Knowledge andbehaviorSo, the medical student has unsatisfactory knowledge, inappropriate behavior Study done inKarbala found There is no statistical association between age, education, marital status or occupation and the mean practice score (P value>0.05) (7) .…”
Section: Deficiencymentioning
confidence: 98%
See 3 more Smart Citations